Strategic Management in Improving the Quality of Education in Boarding School - Ade Iskandar; Ibnu Rusydi; Husna Amin; Muhammad Nur Hakim; Habyb Amirul Haqq (STAI Hubbulwathan Duri, 2022)
This article was descriptive qualitative research. The data is collected through interviews, observation, triangulation, documentation, and analyzed by descriptive analysis. This article aims to determine the process of planning, implementing, and evaluating strategic management in improving the quality of education at a Boarding School. This article on strategic management in improving the quality of education at Boarding School shows that: (1) Strategic planning at Boarding School includes four activities, namely developing the school's vision, mission, and goals, short-term planning, long-term planning, and medium term, identification of internal and external factors, and strategy formulation. (2) The implementation of strategic management includes four activities determining school policies, motivating education staff and educators, allocating human resources appropriately, and developing a strategic culture. (3) Evaluation of strategic management includes three activities: monitoring from planning to implementation, measuring individual and madrasa performance, and taking corrective steps.